Nomenclatural types of Hieracium (Asteraceae) species described from the Balearic Islands (Spain) and several related taxa - Ferrer-Gallego, P. Pablo; Mateo, Gonzalo; Rosselló, Josep A.; Sáez, Llorenç (Phytotaxa, 2021)
A nomenclatural revision of the genus Hieracium in the Balearic Islands (Spain) is presented and the typification of five names: H. aragonense Scheele, H. balearicum Arvet‑Touvet, H. elisaeanum Arvet-Touvet ex Willkomm, H. majoricanum Arvet-Touvet and H. microscapum Arvet-Touvet, is discussed. The names are lectotypified using specimens preserved at COI, GRM, and P herbaria. Several comments for the names H. cataractarum Arvet-Touvet & Huter and H. praecox subsp. brachypus Freyn in Porta & Rigo are also provided.